Complex Forearm Fracture with Osteomyelitis: A Case Report of Successful Treatment Using the Ilizarov Technique (Central Medical College Journal, 2025)
Background: Complex forearm fractures in pediatric patients, particularly those complicated by osteomyelitis; require a multidisciplinary approach to achieve favorable outcomes. This case report presents the successful management of a 13-year-old boy with a Gustilo-Anderson Grade IIIA open fracture of the left forearm complicated by methicillin-resistant Staphylococcus aureus (MRSA)-associated osteomyelitis. Initial infection control was achieved through fasciotomy, debridement, and targeted antibiotic therapy. Definitive reconstruction utilizing the Ilizarov ring fixator facilitated distraction osteogenesis, addressing bone defects and restoring function. This report highlights the effectiveness of the Ilizarov technique in managing complex cases involving infection and significant bone loss, emphasizing the importance of timely intervention, infection control, and rehabilitation in achieving excellent clinical and functional outcomes.Central Medical College Journal Vol 8 No 2 July 2024 Page: 102-106